Association of the dietary index for gut microbiota with sleep disorder among US adults: the mediation effect of dietary inflammation index - Li, Yingying; Pan, Fang; Shen, Xiaofei (Frontiers in Nutrition, 2025)
BackgroundPrevious studies have confirmed the relationship between gut microbiota and sleep disorders, characterized by the persistent inability to achieve adequate sleep, with dietary composition playing a key role in maintaining microbiota homeostasis. Our study aims to explore the relationship between the newly proposed Dietary Index for Gut Microbiota (DI-GM) and sleep disorders, as well as whether the Dietary Inflammatory Index (DII) mediates this relationship.MethodsThis study is based on data from 30,406 participants in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018, a cross-sectional survey that represents the U.S. adult population. We used multivariable logistic regression models to examine the relationship between DI-GM and sleep disorders. Subgroup interaction analyses were conducted to assess the stability of the results. Mediation analysis was employed to explore the effect of the Dietary Inflammatory Index (DII) on the relationship between DI-GM and sleep disorders.ResultsThe DI-GM score was significantly negatively correlated with sleep disorders. After adjusting for covariates, each unit increase in DI-GM was associated with a 5% reduction in the prevalence of sleep disorders (p < 0.001). Additionally, there was a trend toward a decrease in the prevalence of sleep disorders with increasing DI-GM (trend p < 0.05). Dose–response curve analysis revealed a linear relationship between DI-GM and sleep disorders, with higher DI-GM scores being associated with lower prevalence of sleep disorders. DII was positively correlated with sleep disorders (p < 0.001) and decreased as DI-GM increased (β = −0.37, p < 0.001). Mediation analysis showed that DII significantly mediated the relationship between DI-GM and sleep disorders, with a mediation proportion of 27.36% (p < 0.001).ConclusionThe results of this study indicate that the DI-GM score was significantly negatively correlated with sleep disorders. A higher DI-GM score is associated with a lower incidence of sleep disorders, while the DII significantly mediated the relationship between DI-GM and sleep disorders. Specifically, an increase in DII may attenuate the protective effect of DI-GM on sleep disorders.